HUBUNGAN ASUPAN NATRIUM, FREKUENSI DAN DURASI AKTIVITAS FISIK TERHADAP TEKANAN DARAH LANSIA DI PANTI SOSIAL TRESNA WERDHA BUDI SEJAHTERA DAN BINA LARAS BUDI LUHUR KOTA BANJARBARU, KALIMANTAN SELATAN - Abdurrachim, Rijanti; Hariyawati, Indah; Suryani, Nany (GIZI INDONESIA, 2016)
Elderly tends to face health problems caused by a decrease in body functions due to aging. One of the most health problems experienced by elderly is in cardiovascular system like hypertension. Factors influenced blood pressures are overweight, less physical activity, and eating high sodium foods. This study aimed to determine the relationship between sodium intake, frequency and duration of physical activity to blood pressure of elderly at Tresna Werdha Budi Sejahtera and Bina Laras Budi Luhur nursing homes in Banjarbaru. This research used cross sectional design. Pearson test were applied (α = 0.05). This study involved 65 elderly aged 60-74 years, 28 males (43%) and 37 females (57%). Data were collected using questionnaires. Nutrient contents were obtained using 1x24 hour food recall for 2 days included weekend. The result of Pearson test indicated that there was a significant positive correlation between sodium intake with systolic (p <0.05) and diastolic (p <0.05) levels. Moreover, there was a significant negative correlation between the frequency of physical activity with systolic (p < 0.05) and diastolic (p <0.05) levels; there was a significant negative correlation between physical activity duration and sistolic blood pressure (p<0.05). However, there was no significant correlation between physical activity duration and diastolic blood pressure. It was suggested that health workers should improve health promotion program using posters and do counseling about healthy lifestyles, i.e. suggesting people to avoid high sodium foods and do physical activity regularly.